The Correlation of Core Stability and Muscle Imbalance to Identify Injury Risk Futsal Players Porprov Kendal - Galeh Purwatama; Wahyuni Wahyuni (UNIB Press, 2023)
Exercise is one of the physical exercises commonly practiced by people to improve physical condition. Every sport has a risk of injury or (sport injury). One of them is futsal sports, sport injury is a type of injury during training or competition that causes injury due to external factors such as tackling, collisions, collisions and internal factors such as poor core stability, muscle weakness, muscle imbalance and excessive use of muscles or ligaments. Knowing the between core stability and muscle imbalance to identify the risk of injury for Kendal porprov futsal players. This type of research uses analytical Observational research design with Cross Section design. The population in this study were all Kendal porprov futsal players with sampling using Total Sampling technique, a sample of 20 respondents. Data analysis in this study used the Kendall tau correlation test. There is a correlation between Core Stability and Injury Risk where the p-value p = 0.000 (p < 0.05). And there is a correlation in muscle imbalance with the risk of injury where the p-value p = 0.009 (p < 0.05). There is a correlation between core stability and muscle imbalance to identify the risk of injury for Kendal porprov futsal players.